Afraid of repeated infections? The influence of social comparative tendency on tourism satisfaction in the post-COVID-19 era: the mediation role of counterfactual thinking and the moderation role of risk perception - Yibo Xie; Wenbin Ma; Lu Wu (Cogent Social Sciences)
In this paper, the roles of upward counterfactual thinking and their perception of COVID-19 risk in the influence of social comparison tendency on travel satisfaction was investigated. The study follows the design of 3 (social comparison tendency: high, low and medium) by 2 (perceived risk degree of COVID-19: high and low). The findings are as follows: (1) There are significant differences in the tourism satisfaction of individuals with different social comparison tendencies: the tourism satisfaction of individuals with low social comparison tendencies is significantly higher than that of the other two groups, and the tourism satisfaction of individuals with high social comparison tendencies is higher than that of individuals with medium social comparison tendencies; (2) The influence of social comparison tendency on tourism satisfaction is mediated by upward counterfactual thinking and moderated by the perception of COVID-19 risk. These findings help the tourism industry to better understand consumers’ psychological needs and behavior patterns, so as to design tourism products and marketing strategies that better meet consumers’ expectations. Especially after the epidemic, understanding consumers’ risk perception and its impact on satisfaction can help the tourism industry to cope with the potential health crisis more effectively, improving the quality of tourism services and enhance consumers’ confidence.